Isolation and characterization of fecal bacteria capable of 16 alpha-dehydroxylating corticoids. - Bokkenheuser, V D (1980)
For more than a decade it has been known that the fecal flora of humans and rats includes organisms capable of 16 alpha-dehydroxylating corticoids, but their identity has remained unknown. To isolate these organisms, Mueller-Hinton agar plates were seeded with fresh feces from Proteus-free rats and incubated anaerobically. On an average, 1 of every 35 colonies consisted of organisms synthesizing 16 alpha-dehydroxylase. Isolation of the individual colonies yielded two obligate anerobes, strains 144 and 146, which elaborated the enzyme. The steroid transformation could be attained by the microbial culture alone in prereduced media or in aerobic media in the presence of Escherichia coli. Although both strains were phenotypically similar to Eubacterium lentum, they differed between themselves in their enzymatic equipment.